1999
DOI: 10.1093/brain/122.4.741
|View full text |Cite
|
Sign up to set email alerts
|

A clinical pathological comparison of three families with frontotemporal dementia and identical mutations in the tau gene (P301L)

Abstract: We investigated three separate families (designated D, F and G) with frontotemporal dementia that have the same molecular mutation in exon 10 of the tau gene (P301L). The families share many clinical characteristics, including behavioural aberrations, defective executive functions, language deficits, relatively preserved constructional abilities and frontotemporal atrophy on imaging studies. However, Family D has an earlier mean age of onset and shorter duration of disease than Families F and G (49.0 and 5.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
142
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(159 citation statements)
references
References 32 publications
15
142
2
Order By: Relevance
“…However, the P301L subjects also showed widespread loss including the frontal lobes but had a relatively short time from onset to scan of only 4 years, which suggests either that frontal lobe loss is an early feature of P301L mutations or P301L mutations may have a more rapidly progressive disease, and therefore atrophy has spread further through the brain in the same time. Previous studies have typically reported both temporal and frontal atrophy in P301L patients, 8,[26][27][28] and others have suggested that P301L subjects are rapidly progressive. 8 We also identified severe involvement of the basal ganglia in both the P301L and V337M subjects.…”
Section: Resultsmentioning
confidence: 96%
“…However, the P301L subjects also showed widespread loss including the frontal lobes but had a relatively short time from onset to scan of only 4 years, which suggests either that frontal lobe loss is an early feature of P301L mutations or P301L mutations may have a more rapidly progressive disease, and therefore atrophy has spread further through the brain in the same time. Previous studies have typically reported both temporal and frontal atrophy in P301L patients, 8,[26][27][28] and others have suggested that P301L subjects are rapidly progressive. 8 We also identified severe involvement of the basal ganglia in both the P301L and V337M subjects.…”
Section: Resultsmentioning
confidence: 96%
“…Clinically, FTDP-17 phenotypes appear to be quite variable, not only between mutations, but also within a single mutation and even within individual families either with intronic (60) or missense mutations (61). Despite the variability, some similarities are observed, as for example parkinsonism is present more frequently in families with intronic mutations (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…To underscore this point, Kindred 2 had several members with primarily amnestic difficulties, one individual with PPA, another with FTDP, and one individual presented with amnestic complaints which quickly evolved into FTD. Phenotypic heterogeneity has been seen both within families and among families having identical mutations in MAPT as well (Bird et al 1999). …”
Section: Clinical Considerationsmentioning
confidence: 99%